Reading development of late talking toddlers with and without familial risk for dyslexia : a follow up study from age 2 to 15 - Psyridou, Maria (2015)
Expressive language delay is one of the most frequent concerns for parents and health care providers, and it is also one of the most common reasons that young children are referred for evaluation. In the present study, it was examined whether late-talkers with and without familial risk for dyslexia have weaker reading fluency and comprehension at school age (grades 2, 3, 8 and 9) than typically developing, agematched children. The sample of the study was 200 Finnish-speaking children, who were divided into 5 subgroups: 1) Risk Group with no Delay, 2) Risk Group with Expressive Language Delay, 3) Risk Group with Expressive and Receptive Language Delay, 4) Control Group with Expressive Language Delay, 5) Control Group with no Delay. The children belonging to the family risk group have a family history of dyslexia and as a result they are at risk for reading difficulties. The results showed that late talkers had problems particularly in reading comprehension but problems were persistent only if they had also receptive vocabulary problems. On the other hand, family risk for dyslexia was linked to reading fluency problems but only if the children had both expressive and receptive vocabulary problems. As a result, it seems that expressive delay only is not informative enough considering school age reading development and it seems that late talking could be a persistent risk factor for reading development only if it is combined with receptive language delays.